Bcl-2 Immunoexpression as Radiotherapy Response Predictor in Undifferentiated Nasopharynx Carcinoma - Beby S. Damayanti; . Afiati; Abdul H. Hassan; Bethy S. Hernowo (Journal of Medicine and Health, 2015)
Nasopharyngeal carcinoma (NPC) is an epithelial malignancy originating from the surface of the lateral and posterior wall of the nasopharynx. Bcl-2 is an oncoprotein that plays an important role in disrupting the process of apoptosis. Expression of Bcl-2 in biopsy samples of undifferentiated NPC also related to the nature of more aggressive tumor mass and unfavorable clinical radiotherapy response. The purpose of this study was to assess the relationship of Bcl-2 expression with radiotherapy response in undifferentiated NPC. The method of this study areusing 40 samples of paraffin blocks were diagnosed as undifferentiated NPC by histopathologic examination with H&E staining. The samples were divided into 2 groups who respond and do not respond to radiotherapy. All samples examined by Bcl-2 immunohistochemistry and the expression willanalyzed and assess therelationship to radiotherapy response. Of the 40 cases of undifferentiated NPC show imunoekspresi Bcl-2 positive in 39 cases (97.5%) and 1 case (2.5%) negative from response group. The results of statistical analysis of the Bcl-2 obtained significant results with p value <0.05 so we can conclude there is a relationship between Bcl-2 expression with radiotherapy response. Conclusion, Bcl-2 can be used as a predictor for the success of radiotherapy in undifferentiated NPC.Â Keywords: Bcl-2, undifferentiated NPC, radiotherapy response